(untitled) (The Research of Medical Science Review, 2025)
Background: Anemia in antenatal females is a serious outcome of maternal and infant mortality and morbidity. Anemia is a blood disorder in which the blood has a reduced ability to transport oxygen due to a lower number of red blood cells in the body. Worldwide the prevalence of anemia in pregnant women is 41.8% as per World Health Organization (WHO) findings Objectives: To determine the knowledge and socioeconomic factors associated with anemia in pregnant women at Liaquat University hospital Jamshoro Sindh. Methods: The descriptive cross sectional survey type method was used. The sample size of the study was (n=335). The sample was selected using purposive sampling method. The data analysis was done on SPSS software version 21. Results: The results indicates that significant statistical association between ethnicity and anemic status (p= 0.032). The residential area and monthly income also proves to have a significant association with anemic status (p= 0.005, p=0.001), while the religion, job status and education do not have any significant association with anemia status. Conclusion: This comprehensive study offers the valuable insight for healthcare policymakers and other practitioner to tailor the intervention and to run the public health programs more effectively. By addressing the association of anemia in pregnant women and the various socioeconomic contexts, we can make various substantial steps towards improving health and wellbeing of pregnant women.